2011
DOI: 10.1068/p6868
|View full text |Cite
|
Sign up to set email alerts
|

Depth Interval Estimates from Motion Parallax and Binocular Disparity beyond Interaction Space

Abstract: Static and dynamic observers provided binocular and monocular estimates of the depths between real objects lying well beyond interaction space. On each trial, pairs of LEDs were presented inside a dark railway tunnel. The nearest LED was always 40 m from the observer, with the depth separation between LED pairs ranging from 0 up to 248 m. Dynamic binocular viewing was found to produce the greatest (ie most veridical) estimates of depth magnitude, followed next by static binocular viewing, and then by dynamic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Justification for this is sometimes given by the often made, yet unsubstantiated, claim that stereoscopy is not an effective cue to depth beyond approximately 6 m (Gregory, 1966;Palmer, 1999), and the observation that the range of distances relevant to driving stretch far beyond this extent-for example, car-following distances of 7-30 m (Piao & McDonald, 2003). In fact, when explicitly investigated, stereoscopy does provide useful information at larger distances (Allison, Gillam, & Vecellio, 2009) up to at least 248 m in real-world viewing conditions (Gillam, Palmisano, & Govan, 2011;Palmisano, Gillam, Govan, Allison, & Harris, 2010), and hence is a very relevant cue for the visual range over which information is presented during driving tasks. Several driving studies have shown advantages of stereoscopic presentation.…”
Section: Implications For Driving Simulator Designmentioning
confidence: 99%
“…Justification for this is sometimes given by the often made, yet unsubstantiated, claim that stereoscopy is not an effective cue to depth beyond approximately 6 m (Gregory, 1966;Palmer, 1999), and the observation that the range of distances relevant to driving stretch far beyond this extent-for example, car-following distances of 7-30 m (Piao & McDonald, 2003). In fact, when explicitly investigated, stereoscopy does provide useful information at larger distances (Allison, Gillam, & Vecellio, 2009) up to at least 248 m in real-world viewing conditions (Gillam, Palmisano, & Govan, 2011;Palmisano, Gillam, Govan, Allison, & Harris, 2010), and hence is a very relevant cue for the visual range over which information is presented during driving tasks. Several driving studies have shown advantages of stereoscopic presentation.…”
Section: Implications For Driving Simulator Designmentioning
confidence: 99%
“…For example, Gregory (1966) claimed that we are ''effectively one-eyed for distances greater than about twenty feet'' (p. 53). However, stereopsis is now known to contribute to depth perception at considerably larger distances (see Allison, Gillam, & Vecellio, 2009;Gillam, Palmisano, & Govan, 2011;Palmisano, Gillam, Govan, Allison, & Harris, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small amount of bits required for depth information, transmitting additional one-view depth data for basic-quality applications and even one or two more views of texture plus depth for high-quality services does not seem to be a disaster for current 2D broadcast infrastructure. With more homogeneous regions, depth maps generally require much less bitrate than the associated texture images using the same compression technique [86,96]. Some preliminary studies show that depth can be assigned with around 25 % of the corresponding texture bitrate for achieving the best synthesis quality [86], given a total bandwidth.…”
Section: D Video Transmission and Storagementioning
confidence: 99%
“…The DVB-C [96] specification was developed in 1994 by the DVB Consortium for broadcast delivery over Hybrid Fiber Coax (HFC) cable networks and Master Antenna Television (MATV) installations. At the moment, this standard is deployed worldwide in cable systems ranging from the larger CATV networks down to smaller SMATV systems.…”
Section: D-tv Over Cable Network: Dvb-c/c2mentioning
confidence: 99%
See 1 more Smart Citation